THE CHARACTERISTICS OF PRE-CENOZOIC BASEMENT STRUCTURES OF THE TRUONG SA ARCHIPELAGO AND ADJACENT AREAS - Minh, Nguyen Quang; Dung, Tran Tuan (Vietnam Journal of Marine Science and Technology, 2017)
Truong Sa archipelago is located in the South of East Vietnam Sea, thus impacted by the strong tectonic activity in the Cenozoic. Pre-Cenozoic basement is strongly differentiated and has complex structures. For interpretation of tectonic evolution in the Cenozoic, the up-down blocks, basement depth and fault systems of the basement must be determined. 3D gravity anomaly model is a new approach to solve the structural problem above. In this paper, the gravity gradient tensor method is applied to determine the basement depth; the low-frequency filter method and the maximum horizontal gradient method are used to determine the fault systems of the basement. Based on basement depth and fault systems, the basement is divided into the structural units. The study results show that the basement depth difference between model and well data is approximately 3%. Basement structures are differentiated and complicated, the basement depth is changed from a few km near shore to over 10 km in Tu Chinh - Vung May Basin; the major direction of fault system is Northeast - Southwest